2013
DOI: 10.1037/a0032551
|View full text |Cite
|
Sign up to set email alerts
|

Moderation effects of perfectionism and discrimination on interpersonal factors and suicide ideation.

Abstract: This study examined the moderating effects of 3 risk factors-perfectionistic personal discrepancy, perfectionistic family discrepancy, and discrimination-on the associations between interpersonal risk factors (i.e., perceived burdensomeness and thwarted belongingness) and suicide ideation in a sample of 466 Asian international students studying in the United States. We focused specifically on perceived discrimination and maladaptive perfectionism as moderating risk factors to Joiner's (2005) interpersonal theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 61 publications
7
95
0
Order By: Relevance
“…Having higher family standards has been associated with higher self-esteem (Wang, 2010), and family discrepancy has been linked with depressive and anxiety symptoms (Ortega, Wang, Slaney, Hayes, & Morales, 2014). In addition, family discrepancy has been linked to suicidal risks, serving as a moderator that intensifies the positive associations between interpersonal risk factors (i.e., perceived burdensomeness and thwarted belongingness) and suicide ideation (Wang, Wong, & Fu, 2013). Thus, this maladaptive form of perfectionism from one's family is an important factor to examine among LDS individuals who believe that family is at the core of its values.…”
Section: Perfectionismmentioning
confidence: 98%
“…Having higher family standards has been associated with higher self-esteem (Wang, 2010), and family discrepancy has been linked with depressive and anxiety symptoms (Ortega, Wang, Slaney, Hayes, & Morales, 2014). In addition, family discrepancy has been linked to suicidal risks, serving as a moderator that intensifies the positive associations between interpersonal risk factors (i.e., perceived burdensomeness and thwarted belongingness) and suicide ideation (Wang, Wong, & Fu, 2013). Thus, this maladaptive form of perfectionism from one's family is an important factor to examine among LDS individuals who believe that family is at the core of its values.…”
Section: Perfectionismmentioning
confidence: 98%
“…Research examining young adults raised in collectivistic cultures has found that a heightened tendency to perceive that they failed to meet their family's standards was associated with an intensification of the effect of thwarted belongingness on suicidal ideation. 35 Thus, in a culture that emphasizes community and self-suppression, young adults feeling disconnected from others may be more vulnerable to suicidal desire. Furthermore, individuals from collectivistic cultures tend to be reluctant to discuss symptoms of mental illness and seek treatment, 36 which may exacerbate symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Feelings of liability inherent in perceived burdensomeness are also associated with self‐hatred, shame, and low self‐esteem (Van Orden et al., ). Perceived burdensomeness has received considerable support as a risk factor for suicide ideation in a variety of populations (e.g., Cukrowicz, Cheavens, Van Orden, Ragain, & Cook, ; Wang, Wong, & Fu, ), though only two studies have examined and found links between perceived burdensomeness and elevated suicide ideation in psychiatric inpatients (de Catanzaro, ; Monteith, Menefee, Pettit, Leopoulos, & Vincent, ). In cross‐sectional studies, perceived burdensomeness mediated the relation between depressive symptoms and suicide ideation in older adults (Jahn, Cukrowicz, Linton, & Prabhu, ), as well as the relations between a variety of risk factors (e.g., problematic alcohol use, childhood emotional abuse) and suicide ideation in college students (Lamis & Malone, ; Puzia, Kraines, Liu, & Kleiman, ).…”
mentioning
confidence: 99%